1996
DOI: 10.1080/15216549600201542
|View full text |Cite
|
Sign up to set email alerts
|

Transblot identification of avidin‐interacting proteins in rat salivary glands

Abstract: SUMMARY: Blotting of rat parotid gland proteins separated by SDS-PAGE and transferred to Immobilon transfer membranes revealed that avidin-peroxidase conjugate interacted with bands having estimated molecular weights of 72, 74, and 120 kDa. Even at the lowest concentration of avidin-peroxidase used in the general ABC method (1:2000 dilution), three bands were clearly discernible.The staining reaction of parotid gland proteins was eliminated on preincubating the proteins with native avidin.The staining reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…One of the reasons for this non-specific reaction is the presence of endogenous biotin (Satho et al 1992) and biotin-containing proteins in tissues or cells (Fishleder et al 1982;Bussolati and Gugliotta 1983;Jones et al 1987;Haneji and Koide 1988). Using avidin-horseradish peroxidase (HRP), streptavidin-fluorescein isothiocyanate (FITC), and avidin-colloidal gold conjugate as probes, we have already demonstrated that avidin-interacting proteins are present in clam oocytes and in some mammalian tissues Koide 1988, 1989;Haneji et al 1991Haneji et al , 1993Shirakawa et al 1996). Although the non-specific interaction is observed, the ABC method is still useful in various biochemical and histochemical studies (Wilchek and Bayer 1988).…”
Section: Introductionmentioning
confidence: 95%
“…One of the reasons for this non-specific reaction is the presence of endogenous biotin (Satho et al 1992) and biotin-containing proteins in tissues or cells (Fishleder et al 1982;Bussolati and Gugliotta 1983;Jones et al 1987;Haneji and Koide 1988). Using avidin-horseradish peroxidase (HRP), streptavidin-fluorescein isothiocyanate (FITC), and avidin-colloidal gold conjugate as probes, we have already demonstrated that avidin-interacting proteins are present in clam oocytes and in some mammalian tissues Koide 1988, 1989;Haneji et al 1991Haneji et al , 1993Shirakawa et al 1996). Although the non-specific interaction is observed, the ABC method is still useful in various biochemical and histochemical studies (Wilchek and Bayer 1988).…”
Section: Introductionmentioning
confidence: 95%